Factors associated with the low back pain-related attitudes and beliefs of physical therapists. (April 2022) - Rufa, Adam; Dolphin, Michelle; Adams, Kyle; Brooks, Gary
Abstract: Background: Clinicians who believe in a strong connection between pain and disability, and who have biomedically oriented beliefs recommend less physical activity, more time off work, and promote unhelpful beliefs in patients. Understanding how these beliefs develop may assist in identifying ways to reduce unhelpful beliefs in clinicians. Objective: To identify factors that are associated with the LBP-related attitudes and beliefs of US-based physical therapists. Design: Cross-sectional design Method: An electronic survey was sent to US-based physical therapists. Attitudes and beliefs were measured using the Health Care Providers' Pain and Impairment Relationship Scale (HC-PAIRS) and the Pain Attitudes and Beliefs Scale for Physiotherapists (PABS-PT), pain science knowledge was measured using the Neurophysiology of Pain Questionnaire (NPQ), and professional and demographic information were collected. Results: Completed surveys were obtained from 420 physical therapists. More helpful attitudes and beliefs were associated with board certification in orthopedics or sports, higher NPQ scores, and working in a hospital-based clinic. Less helpful attitudes and beliefs were associated with working in private practice and a personal history of LBP that had a minimum or significant impact on life. The factors included in this study explained 16.8% of the variability in HC-PAIRS scores (p < .001), 13% of the variability in PABS-BM scores (p < .001), and 8.3% of the variability in PABS-BPS scores (p < .001). Conclusion: Several modifiable and non-modifiable factors are associated with the LBP-related attitudes and beliefs of US physical therapists. Highlights: Post-graduation education factors were associated with more helpful beliefs. LBP that impacted life had the strongest association with unhelpful beliefs. Certification and knowledge had the strongest association with helpful beliefs. Physical therapists in outpatient private practice were more biomedically oriented. Physical therapists in hospital settings were more biopsychosocially oriented.